On Some Issues of an Expert Study of the Readiness and Cost of Design Documentation for Construction Projects - F. G. Aminev; S. A. Zamyatin (Теория и практика судебной экспертизы)
The article discusses some aspects of the study of the readiness and cost of design documentation of construction projects in forensic examination; establishes the objects of such examination; describes their quality criteria. The authors analyze the most common mistakes in forensic research, as well as the possibilities for solving terminological problems and integrating conceptual fields of different sciences. They also show the perspectives of applying the theory of qualimetry and the economic theory of utility in an expert study of the readiness and cost of design documentation for construction projects. A general comprehensive assessment of project quality has been developed: special attention has been paid to absolute and relative indicators of the readiness of project documentation.The authors propose a reasonable version of the calculation justification for the degree of readiness of project documentation, they show the advantages of the suggested methodological approach, and first of all, the possibility of applying computer processing of results and the relative simplicity of the software calculation algorithm.